(3SDGd hLhGH aj GdRjJ EPG hbYJ ajg fLGSIs - (3eMeO GdNdjdjs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdESdGe eHfjkG Ydi GdjSQ s
(3BNQgG (B:s
(3hEPG VGb GdCeQ GJSY hGddg JYGdi CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQGSMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs